LOCAL TECHNOLOGIES USED IN THE TEACHING OF THE SUBJECT OF THE UZBEK INDUSTRY - Yuldoshova Yulduz (Scholar Express Journal, 2023)
The article focuses on the use of local technologies in teaching the subject of the Uzbek industry. The article discusses the importance of using local technologies in teaching and provides an overview of the methods used in the study. The results of the study are presented, along with a discussion of the implications for teaching the subject of the Uzbek industry. Finally, the article concludes with suggestions for further research.
Keywords: local technologies; teaching; Uzbek industry; methods